Epigenetic Application of ATAC-Seq Based on Tn5 Transposase Purification Technology - Wangchun Li; U Tim Wu; Yu Cheng; Yanhao Huang; Lipeng Mao; Menghan Sun; Congling Qiu; Lin Zhou; Lijuan Gao (Genetics Research)
Background. Assays of transposase accessible chromatin sequencing (ATAC-seq) is an efficient assay to investigate chromatin accessibility, which depends on the activity of a robust Tn5 transposase to fragment the genome while cutting in the sequencing adapters. Methods. We propose reliable approaches for purifying hyperactive Tn5 transposase by chitin magnetic bead sorting. Double-stranded DNA of J76 cells and 293T cells were digested and subjected to tagmentation as test samples with Tn5 transposase, and libraries were established and sequenced. Sequencing data was then analyzed for peak calling, GO enrichment, and motif analysis. Results. We report a set of rapid, efficient, and low-cost methods for ATAC-seq library construction and data analysis, through large-scale and rapid sequencing. These methods can provide a reference for the study of epigenetic regulation of gene expression.